A prospective study on effect of maternal BMI on fetal outcome - Sharma, Bali Ram; Sharma, Reena; Dogra, Poojan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The extremes of BMI have a major impact on pregnancy outcomes. The objective of this study was to assess antenatal, intra-partum complications, perinatal outcome in pregnant women with high BMI. Methods: This study was conducted in Department of Obstetrics and Gynecology, Kamla Nehru State Hospital for Mother and Child IGMC Shimla, on 1000 women attending antenatal outpatient department over one year w.e.f. 01-05-2011 to 30-04-2012. Detailed information regarding different variables like maternal age, parity, education status, occupation socioeconomic status and weight gain during pregnancy were recorded on a proforma, master chart framed and analyzed using Student’s t test. Results: The study observed that both being overweight and underweight predisposes women to complicated pregnancies. The incidence of preterm is more in underweight women and post- dated deliveries increased with increase in BMI. Incidence of stillbirth was maximum in obese women. Incidence of low birth weight babies was more among underweight and the incidence of macrosomia was more in obese women. Conclusions: Maternal BMI have strong association with pregnancy complications and outcome.